'Don't mention (them) again'! Shame, the Black Eagles Incident and Winds of September. Issue 3 (1st September 2015) - Chen, Po-hsi
The 1997 Black Eagles Incident of the Chinese Professional Baseball League (CPBL) marks the Edenic fall in the history of baseball in Taiwan. Since the Black Eagles Incident, the nationalist discourse of glory had been intertwined with the narrative of shame. Having been immersed in the spirit of triumphalism in the early 2000s, baseball in Taiwan was again beset by a series of large-scale game-fixing scandals in the latter half of the 2000s. The neologism mozaiti – 'don't mention again' – was coined as a response by desperate fans. This article reads Lin Shu-yu's 2008 film Jiujiang feng/Winds of September, a baseball story of initiation and disillusion featuring a former professional baseball player's cameo appearance, against this backdrop. The film visually frames a phantasmatic space in which the 'not-to-be-mentioned' fallen hero is staged to perform his failure and guilt. In so doing, his affect of shame is exchanged with his fans' through that cinematically imagined, constructed phantasmatic space. In this sense, the image of baseball in the post-martial-law era is internalized within one's adolescence and familial (especially father-and-son) relationship. In Winds of September, one's faulted youth and troubled family ties are reconciled through coming to terms with the baseball scandal.